Long Non-coding RNA and mRNA Expression Change in Spinal Dorsal Horn After Exercise in Neuropathic Pain Rats - Song, Ge; Zhang, Wei-Ming; Wang, Yi-Zu; Guo, Jia-Bao; Zheng, Yi-Li; Yang, Zheng; Su, Xuan; Chen, Yu-Meng; Xie, Qing; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
Exercise can help inhibition of neuropathic pain (NP), but the related mechanism remains being explored. In this research, we performed the effect of swimming exercise on the chronic constriction injury (CCI) rats. Compared with CCI group, the mechanical withdrawal threshold of rats in the CCI-Swim group significantly increased on the 21st and 28th day after CCI surgery. Second-generation RNA-sequencing technology was employed to investigate the transcriptomes of spinal dorsal horns in the Sham, CCI, and CCI-Swim groups. On the 28th day post-operation, 306 intersecting lncRNAs and 173 intersecting mRNAs were observed between the CCI vs Sham group and CCI-Swim vs CCI groups. Then, the biological functions of lncRNAs and mRNAs in the spinal dorsal horn of CCI rats were then analyzed. Taking the results together, this study could provide a novel perspective for the treatment for NP.